Optimal drain management following complicated laparoscopic cholecystectomy for acute cholecystitis: a propensity-matched comparative study - Seung Jae Lee; In Seok Choi; Ju Ik Moon; Dae Sung Yoon; Won Jun Choi; Sang Eok Lee; Nak Song Sung; Seong Uk Kwon; In Eui Bae; Seung Jae Roh; Sung Gon Kim (Journal of Minimally Invasive Surgery, 2022)
Purpose: This study was performed to investigate the effect of drain placement on complicated laparoscopic cholecystectomy (cLC) for acute cholecystitis (AC). Methods : This single-center retrospective study reviewed patients with AC who underwent cLC between January 2010 and December 2020. cLC was defined as open conversion, subtotal cholecystectomy, adjacent organ injury during surgery, operation time of ≥90 minutes, or estimated blood loss of ≥100 mL. One-to-one propensity score matching was performed to compare the surgical outcomes between patients with and without drain on cLC. Results : A total of 216 patients (mean age, 65.8 years; 75 female patients [34.7%]) underwent cLC, and 126 (58.3%) underwent intraoperative abdominal drainage. In the propensity score-matched cohort (61 patients in each group), early drain removal (≤postoperative day 3) was performed in 42 patients (68.9%). The overall rate of surgical site infection (SSI) was 10.7%. Late drain removal demonstrated significantly worse surgical outcomes than no drain placement and early drain removal for overall complications (13.1% vs. 21.4% vs. 47.4%, p = 0.006), postoperative hospital stay (3.8 days vs. 4.4 days vs. 12.7 days, p < 0.001), and SSI (4.9% vs. 11.9% vs. 31.6%, p = 0.006). In the multivariate analysis, late drain removal was the most significant risk factor for organ space SSI. Conclusion : This study demonstrated that drain placement is not routinely recommended, even after cLC for AC. When placing a drain, early drain removal is recommended because late drain removal is associated with a higher risk of organ space SSI.